2022
DOI: 10.1080/08927936.2022.2051932
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Children with Autism Spectrum Disorder’s Interactions with a Service Dog During Their First Encounter

Abstract: Reports reveal various benefits of animals -especially dogs -for children with Autism Spectrum disorders (ASD). However, not all children with ASD display the same interest in animals. Dogs are the most common species within family households and the only species to be used as service animals. They are also the most commonly used species in animal assisted interventions. Despite the key role that both the interest and the behaviours displayed towards dogs might play in their benefits to children with ASD, no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 82 publications
(119 reference statements)
0
17
0
Order By: Relevance
“…In their process of attributing a service dog to families of children with ASD, organizations such as the Mira Foundation and the Handi’Chiens Asssociation are very attentive to the pairing of the child and the SD (e.g., compatible personalities, the SD shows behaviors adapted to the child’s specificities, the child shows attraction to the SD) in order to ensure optimal chances that both will build a significant relationship. This attention to pairing seems relevant in order to ensure that the integration of their SD leads to the expected benefits, and seems even more important considering that not all children with ASD show the same interest toward SDs and not all develop a significant relationship with their SD [ 73 – 75 , 78 , 80 , 104 ]. Various factors, including age and the severity of ASD, have been identified as contributing to the variability in the interest and interaction of children with ASD toward animals [ 80 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In their process of attributing a service dog to families of children with ASD, organizations such as the Mira Foundation and the Handi’Chiens Asssociation are very attentive to the pairing of the child and the SD (e.g., compatible personalities, the SD shows behaviors adapted to the child’s specificities, the child shows attraction to the SD) in order to ensure optimal chances that both will build a significant relationship. This attention to pairing seems relevant in order to ensure that the integration of their SD leads to the expected benefits, and seems even more important considering that not all children with ASD show the same interest toward SDs and not all develop a significant relationship with their SD [ 73 – 75 , 78 , 80 , 104 ]. Various factors, including age and the severity of ASD, have been identified as contributing to the variability in the interest and interaction of children with ASD toward animals [ 80 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…This attention to pairing seems relevant in order to ensure that the integration of their SD leads to the expected benefits, and seems even more important considering that not all children with ASD show the same interest toward SDs and not all develop a significant relationship with their SD [ 73 – 75 , 78 , 80 , 104 ]. Various factors, including age and the severity of ASD, have been identified as contributing to the variability in the interest and interaction of children with ASD toward animals [ 80 , 105 ]. For example, in their study on pets in the families of children with ASD, Grandgeorge et al [ 80 ] found that children with ASD who experienced the arrival of a pet in their homes at 4–5 years of age developed a stronger relationship with their pet, and show a significant improvement in their prosocial behaviors; which was not the case for children with ASD whose family owned a pet prior to their birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important line of future research will be to identify any factors – human or canine – that may be predictive of successful bonding between service dog and child, or whether there are cases where it is in fact more helpful for the service dog to form a primary bond with the caretaker instead. Some initial work has begun to characterize first interactions ( 49 ), and similar methods could be employed in a longitudinal design to begin identifying associations between early interactions and future bond strength. Ultimately, these findings could provide critical insights for service dog providers and health care practitioners to improve recommendations as to whether a service dog intervention would be appropriate, and if so, how to maximize efficacy.…”
Section: Discussionmentioning
confidence: 99%